Service Quality Development Strategy for Customers of Baitul Maal Wat Tamwil (BMT) Sahara Tulungagung - Nugraheni Fitroh Rezqi Syakarna; Fatkhur Rohman Albanjari (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2023)
BMT Sahara is an Islamic financial institution whose operational target focuses on the small and medium enterprises (SMEs) sector. To increase BMT's market share, it is necessary to analyse what factors influence people's interest in becoming customers at BMT. One of the factors is the quality of service BMT Sahara provides to its customers. Good service must be accompanied by a qualified strategy to support the success of a BMT and maintain its image in the broader community. So the quality of service for customers needs to be improved. This is very important considering the very large role of customers in contributing revenue directly or indirectly to continue supporting BMT Sahara's existence. Â